TLR-2 gene methylation in peripheral blood monocytes from apical periodontitis individuals: A cross-sectional study - Bordagaray, María José; Fernández, Alejandra; Pellegrini, Elizabeth; Garrido, Mauricio; Hernández, Patricia; González-Quintanilla, David; Navia, Gabriel; Rehbein, Daniela; Baeza, Mauricio; Gebicke-Härter, Peter J.; Hernández, Marcela (International endodontic journal, 2025)
Aim Apical periodontitis (AP) is a chronic inflammatory disease arising from the contamination of the root canal system. Epigenetic regulation plays a pivotal role in controlling monocyte/macrophage-mediated local and systemic responses to bacterial challenges via toll-like receptors (TLRs). We aimed to explore the relationship between the methylation and expression patterns of TLR-2 in peripheral blood monocytes of individuals with AP and controls. Methodology Cross-sectional study. Otherwise healthy individuals with AP (n = 25) and controls (n = 29) were recruited. Peripheral blood monocytes were isolated from blood samples by Ficoll gradient and negative immunoselection. DNA and RNA were extracted from monocytes. DNA was bisulfite-treated, amplified and sequenced to evaluate the global and cytosine-phosphate-guanine (CpG) single-site methylation pattern of the TLR-2 gene promoter. mRNA relative levels of TLR-2 were assessed by qPCR. The potential associations between AP, TLR-2 DNA methylation and TLR-2 gene expression were explored using generalized structural equation models (GSEM). Results TLR-2 expression was significantly upregulated in peripheral blood monocytes from individuals with AP compared to controls (p = 0.005). Though no differences were found in the global methylation pattern, CpG single sites from the TLR-2 gene were differentially methylated at positions −40 and +24 (p < 0.05). The methylated positions at −40 and −20 in TLR-2 were associated with TLR-2 transcriptional upregulation (p < 0.05). Further evaluation with GSEM analysis showed that AP promoted the methylation of the −40 CpG single site on the TLR-2 gene, which, in turn, upregulated TLR-2. Conversely, the methylation of the −20 CpG single site did not act as a mediator of TLR-2 transcription in AP. Conclusions AP diagnosis activates peripheral blood monocytes via −40 CpG single-site methylation, independently promoting TLR-2 expression.